Efektivitas E-Wom (elektronic word of mouth) dan Digital Marketing Melalui Konten Terhadap Kunjungan Wisatawan Air Terjun Coban Binangun, Plintahan, Pandaan. - Eka Agustin; Mas Oetarjo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Tourism, as a lucrative investment, requires sustainable management for long-term benefits. Despite its scenic beauty, Coban Binangun struggles with low visitor numbers. However, revitalization efforts and digital promotion, particularly through social media, have led to a notable increase in visitors. Electronic Word of Mouth (eWOM) and digital content shared by visitors play pivotal roles in influencing visitation decisions. Leveraging digital marketing and eWOM, Coban Binangun can enhance its promotional reach and boost visitor interest, thereby fostering sustainable tourism growth. The study, conducted in Plintahan Village, Pandaan, Pasuruan, East Java, employed a quantitative approach with non-probability sampling. Variables examined included EWOM, Digital Marketing, Content, and Visitor Arrivals. Likert scale questionnaires were distributed to 97 respondents, with data analyzed using SPSS version 25. Results indicated that EWOM and Digital Marketing significantly impact Visitor Arrivals, whereas Content does not. Respondents viewed EWOM and Digital Marketing positively, contrasting with the negligible impact of Content, aligning with prior research findings. EWOM is perceived to positively influence Visitor Arrivals, underscoring the significant role of Digital Marketing in driving tourism growth, while Content's effect remains insignificant.